2005
DOI: 10.1007/s00431-005-1643-x
|View full text |Cite
|
Sign up to set email alerts
|

The abnormalities of carbohydrate metabolism in Turner syndrome: analysis of risk factors associated with impaired glucose tolerance

Abstract: The oral glucose tolerance test is superior to the fasting and postprandial plasma glucose test for the early detection of abnormalities of carbohydrate metabolism in patients with Turner syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Lastly, although euglycemic-hyperinsulinemic clamp and the intravenous glucose tolerance test with minimal modeling techniques are more accurate than OGTT, this latter is much more physiological than the intravenous tests, mainly because glucose sensors disseminated by the gastrointestinal tract take part in insulin secretion (34). In addition, studies have shown that OGTT is superior to other tests for the diagnosis of early abnormalities of glucose metabolism in these patients (4,11,13). In summary, a broad variety of correlation coefficients between methods based on fasting data of glucose and insulin vs. methods of OGTT-derived values was found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, although euglycemic-hyperinsulinemic clamp and the intravenous glucose tolerance test with minimal modeling techniques are more accurate than OGTT, this latter is much more physiological than the intravenous tests, mainly because glucose sensors disseminated by the gastrointestinal tract take part in insulin secretion (34). In addition, studies have shown that OGTT is superior to other tests for the diagnosis of early abnormalities of glucose metabolism in these patients (4,11,13). In summary, a broad variety of correlation coefficients between methods based on fasting data of glucose and insulin vs. methods of OGTT-derived values was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Euglycemic-hyperinsulinemic clamp technique (12) is well documented as the gold standard for assessment of IR, but it is too laborious, time-consuming, expensive, and technically complicated. The OGTT has been reported to be superior to other tests (hemoglobin A 1c levels, fasting or postprandial blood glucose concentrations) to detect early abnormalities of glucose metabolism in these patients (4,13). Therefore, in this study, the objectives were to assess insulin sensitivity and pancreatic β-cell function in an adult population of Ecuadorian individuals with TS.…”
Section: Introductionmentioning
confidence: 99%
“…Both cross-sectional ( 32 ) and prospective, longitudinal studies ( 3 , 33 ) show that, not surprisingly, the risk of hyperglycemia also increases with age in TS. This phenomenon persists independent of current or prior recombinant GH use ( 33 ), and current ( 33 , 34 ) or prior ( 34 ) estrogen-replacement therapy. Age-related risk of hyperglycemia was also noted in a study of children and adolescents who had never received hormone replacement of any kind ( 16 ).…”
Section: Clinical and Genetic Factors Involved In Hyperglycemia In Tsmentioning
confidence: 99%
“…Currently, most researchers tend to use oral glucose tolerance test (OGTT) to study glucose metabolism in TS patients. Studies have shown that OGTT is superior to other tests (fasting blood glucose, postprandial blood glucose, or glycosylated glycoprotein levels) for diagnosis of early abnormalities of glucose metabolism in these patients (18).…”
Section: Overview Of Glucose Metabolism In Ts Patientsmentioning
confidence: 99%